The relation of weight suppression and BMIz to bulimic symptoms in youth with bulimia nervosa. Issue 1 (December 2016) - Accurso, Erin; Lebow, Jocelyn; Murray, Stuart; Kass, Andrea; Le Grange, Daniel
Abstract Background Weight suppression (WS), which is the difference between a patient's highest and current weight, has been associated with bulimic symptom severity in adults with bulimia nervosa (BN). However, the impact of WS on eating disorder psychopathology in youth with BN is unknown. Methods Participants included 85 youth with DSM-5 BN who presented for outpatient treatment. Current WS was calculated as the difference between highest and current body mass index z-score (BMIz), while greatest WS was the difference between highest and lowest BMIz, both assessed at participants' current height. Separate multivariable linear regressions were conducted to determine if current or greatest WS was significantly associated with frequency of binge eating, compensatory behaviors, or dietary restraint. A secondary analysis was conducted on youth ages 16 and older, given the limitation of assessing WS at current height in younger participants with greater height instability. Results Youth with higher levels of greatest WS (but not current WS) were older, had a longer duration of illness, and reported greater weight and shape concern. When adjusting for BMIz, neither current nor greatest WS was significantly associated with bulimic behaviors or dietary restraint in the full sample. However, in the subset of youth ages 16 and older, current WS moderated the effect of BMIz on binge eating and compensatory behaviors. For youth with high WS, those with a high current BMIz engaged in more frequent binge eating than those with low current BMIz, and the negative impact of BMIz on compensatory behaviors became weaker. Conclusions Our findings suggest that WS is clinically relevant in the presentation of youth with BN, and that it may need to be addressed as one important factor in BN psychopathology. Future studies using growth charts to determine historically highest and lowest BMIz may help to further elucidate the link (or lack thereof) between WS and BN psychopathology in youth.